Access to maternal health services for young women with disabilities in Sub-Saharan Africa: a scoping review protocol - Pebolo, Pebalo Francis; Kimera, Emmanuel; Nkulu Kalengayi, Faustine Kyungu; Namatovu, Fredinah (BMJ open, 2025)
IntroductionYoung women with disabilities (WWDs) face multiple barriers in accessing maternal healthcare services in low-resource settings. Consequently, they are at an increased risk of adverse maternal health outcomes due to young age and having a disability. This review focuses on synthesising evidence regarding the extent of access to maternal healthcare services and the barriers faced by young WWDs in Sub-Saharan Africa.Methods and analysisWe will conduct a scoping review guided by the updated Joanna Briggs Institute methodology for scoping reviews. A systematic search of MEDLINE, EMBASE, Scopus, CINAHL, Web of Science Core Collection, Global Health, African Journal Online and Women’s Studies International will be performed to identify relevant articles published in English from 2007 to 2025. A team of two reviewers will independently screen the retrieved articles for relevancy based on the inclusion criteria, and a thematic synthesis will be undertaken to develop a descriptive analysis.Ethics and disseminationSince this review will only involve the analysis of published data, it does not require ethical approval. The results will be published in a peer-reviewed journal.RegistrationThis review has been registered with the Open Science Framework DOI; https://doi.org/10.17605/OSF.IO/Q7Y8S.